Transformasi Fiskal Menuju Indonesia Emas 2045: Analisis Dampak Kenaikan Pajak Pertambahan Nilai (PPN) 12% dan Peran Krusial Fenomena Cashless Society - Muhammad Ainur Roziqin; Silvia Dewi Nazarina Putri; Miftakhul Janah (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Indonesia has a big aspiration to achieve the status of a developed and sovereign country by 2045, known as Indonesia Emas 2045. A strong and adaptive fiscal foundation is a crucial prerequisite to realize this vision. This article aims to analyze the potential for Indonesia's fiscal transformation in the context of this vision. This study uses a qualitative method with a literature study that collects and analyzes from three research journals, namely from economic journals, money and banking credit journals, and financial inclusion development journals, the journals focus on two significant aspects: the necessity of a policy to increase the Value Added Tax (VAT) rate to 12 percent and the influence of the development of the cashless society phenomenon. Through a synthesis and comparative analysis of various previous studies, this article explores the potential economic and social impacts of the increase in tax rates, and identifies the opportunities and challenges posed by the shift in transaction preferences towards non-cash on state revenues and financial management. The results of this study are expected to provide a comprehensive perspective for policy makers in formulating effective, sustainable, and responsive fiscal strategies to economic and social dynamics in order to achieve Indonesia Emas 2045.